Family employment and child socioemotional behaviour: longitudinal findings from the UK Millennium Cohort Study. Issue 10 (2nd June 2014) - Hope, Steven; Pearce, Anna; Whitehead, Margaret; Law, Catherine
Abstract : Background: Levels of paid employment in two parent and lone parent families have increased in the UK but evidence of its impact on child socioemotional behaviour is limited and inconsistent. Methods: We conducted a longitudinal analysis using the first four sweeps of the Millennium Cohort Study (9 months, 3 years, 5 years and 7 years) to investigate the influence of family employment trajectories in the early years on socioemotional behaviour at 7 years, unadjusted and adjusted for covariates. In addition, mothers' employment was investigated separately. Results: Children from families where no parent was employed for one or more sweeps were at a greater risk of socioemotional problem behaviour compared with those where a parent was continuously employed, even after adjustment for covariates. Children of mothers who were non-employed for one or more sweeps were at greater risk of problem behaviour compared with mothers who were employed at all sweeps. Adjustment for covariates fully attenuated the excess risk for children whose mothers had moved into employment by the time they were 7 years. In contrast, the elevated risk associated with continuous non-employment and a single transition out of employment was attenuated after adjustment for early covariates, fathers' employment, household income and mothers' psychological distress at 7 years, but remained significant. Conclusions: Family and mothers' employment were associated with a lower risk of problem behaviour for children in middle childhood, in part explained by sociodemographic characteristics of families and the apparent psychological and socioeconomic benefits of employment. Results for mothers' transitions in or out of the labour market suggest that child problem behaviour is influenced by current status, over and above diverse earlier experiences of employment and non-employment.